PENGARUH CITRA MEREK, NILAI PRODUK DAN PERSEPSI HARGA TERHADAP KEPUASAN PELANGGAN (Studi Kasus pada Pelanggan Kitty Hijab Lampung) - Sari, Sylvia Devita; Wuryanti, Lestari; Lukman, Iing (Jurnal Jejama Manajemen Malahayati, 2021)
This study aims to determine how the influence of brand image, product value, and price perception on customer satisfaction. The type of data used in this study is quantitative data obtained from the distribution of questionnaires. The population in this study is Kitty Hijab consumers in Bandar Lampung. Sampling using the Slovin formula with a sample of 50 respondents. Data analysis in this study used several methods, including multiple linear regression analysis, namely simultaneous test and partial test. The results of this study indicate that brand image has an effect on customer satisfaction while product value and price perception have no effect on company value. The limitations of the study are only variables customer satisfaction, product value, and price perception. And the object of research is only one thing type and location.Key words : Brand image, product value, price perception, and customer satisfaction